1993
DOI: 10.1007/bf00166737
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent relaxation of porcine pulmonary arteries via 5-HT1C-like receptors

Abstract: In PGF2 alpha-precontracted pulmonary arteries with intact endothelium, 5-hydroxytryptamine (5-HT, 1.0-100 nmol/l) caused a concentration-dependent reversible relaxation, at higher concentrations the contractile response prevailed. In endothelium-denuded vessels relaxation was absent. 5-HT-induced relaxation of precontracted pulmonary arteries was probably mediated by release of an endothelium-derived relaxing factor (EDRF). Preincubation of the arteries with methylene blue or NG-nitro-L-arginine (200 mumol/l)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…This explanation is, however, unlikely in our preparation as we have shown that fetal and 0 ± 24 h rabbit PRAs relax to acetylcholine . 5-HT receptors are known to mediate vasodilation in blood vessels either directly via 5-HT receptors located on the vascular smooth muscle (Cocks & Arnold, 1992;Leung et al, 1996) or indirectly via endothelial released NO (Bodelson et al, 1993;Glusa & Richter, 1993;Glusa & Roos, 1996). We show that, in 4-and 7-day-old rabbit small pulmonary arteries, 5-CT-evoked vasodilation is inhibited by the NO synthase inhibitor L-NAME.…”
Section: -Ht Receptor-induced Vasodilationmentioning
confidence: 56%
See 2 more Smart Citations
“…This explanation is, however, unlikely in our preparation as we have shown that fetal and 0 ± 24 h rabbit PRAs relax to acetylcholine . 5-HT receptors are known to mediate vasodilation in blood vessels either directly via 5-HT receptors located on the vascular smooth muscle (Cocks & Arnold, 1992;Leung et al, 1996) or indirectly via endothelial released NO (Bodelson et al, 1993;Glusa & Richter, 1993;Glusa & Roos, 1996). We show that, in 4-and 7-day-old rabbit small pulmonary arteries, 5-CT-evoked vasodilation is inhibited by the NO synthase inhibitor L-NAME.…”
Section: -Ht Receptor-induced Vasodilationmentioning
confidence: 56%
“…5-HT has previously been shown to elicit endotheliumdependent relaxation in porcine pulmonary arteries (Glusa & Richter, 1993) as well as other, systemic preparations (Bodelson et al, 1993). Using 5-CT, we established that there is 5-HT-receptor-induced vasodilation present in the vessels from the 4-and 7-day-old rabbits.…”
Section: -Ht Receptor-induced Vasodilationmentioning
confidence: 98%
See 1 more Smart Citation
“…Mastomys carcinoid tumor primary cultures, clonal neural-like 1C11* /5HT serotonergic cells and 5-HT 2B receptor transfected LM6 fibroblasts, the 5-HT 2 receptor agonist DOI (or 5-HT, data not shown) always triggers intracellular cGMP accumulation resulting from both cNOS and iNOS activation. Such a link between 5-HT and NO could already be suspected in view of the simultaneous involvement of these two agents in smooth muscle contractility (6,30), vascular contraction (7,31), and related migraine pathogenesis (32). Because 5-HT 2B receptors are present in stomach, intestine, pulmonary smooth muscles, kidney, as well as in myocardium, vascular endothelium, and meningeal tissues (3,33,34), they are obvious candidates to trigger the NO response associated to 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…The blocking potency of ketanserin (effective at 100 nM and higher concentrations) against the relaxant components of 5-HT-induced phasic contractions in the temporal artery is so far consistent with the interaction with 5-HT2c receptors and/or 5-HT2B receptors. It has previously been suggested that endothelial 5-HT2c receptors mediate 5-HT-induced relaxation in porcine pulmonary artery (Glusa & Richter, 1993) and rat jugular vein (Bodelsson et al, 1993), but ketanserin (1 gM) failed to cause antagonism, which is inconsistent with its submicromolar affinity for 5-HT2c receptors and leaves open the possibility of mediation through 5-HT2B receptors. Ellis et al (1995) have indeed recently suggested that endothelium-dependent relaxation of rat jugular vein by 5-HT is mediated through 5-HT2B…”
Section: Effects Of Skandf 103829mentioning
confidence: 99%